2020
DOI: 10.3389/fimmu.2020.01575
|View full text |Cite
|
Sign up to set email alerts
|

Bta-miR-98 Suppresses Replication of Caprine Parainfluenza Virus Type 3 Through Inhibiting Apoptosis by Targeting Caspase-3

Abstract: Caprine parainfluenza virus type 3 (CPIV3) is an emerging respiratory pathogen that affects the sheep and goat industry in China and possibly other countries around the world. Accumulating evidence suggests that microRNAs play important roles in regulating virus-host interactions and can suppress or facilitate viral replication. In this study, we showed that CPIV3 infection induced apoptosis in Madin-Darby bovine kidney (MDBK) cells, as determined by morphological changes and flow cytometry. Caspase activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…13 In addition, the Caprine parainfluenza virus type 3, an emerging respiratory pathogen, triggers apoptosis by targeting CASP3, an effector of apoptosis. 14 In our study, we found a significant relationship between CASP3 Studies reported that as HB 16,17 and lymphocyte 18…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…13 In addition, the Caprine parainfluenza virus type 3, an emerging respiratory pathogen, triggers apoptosis by targeting CASP3, an effector of apoptosis. 14 In our study, we found a significant relationship between CASP3 Studies reported that as HB 16,17 and lymphocyte 18…”
Section: Discussionsupporting
confidence: 56%
“…Also, CASP3 , 8 and 9 activities and the interferon promoter terminal deoxynucleotidyl transferase‐mediated dUTP nick end‐labeling were strongly induced in early infection in H5N1 Cambodia PA‐infected cells that protect uninfected cells from viral infection 13 . In addition, the Caprine parainfluenza virus type 3, an emerging respiratory pathogen, triggers apoptosis by targeting CASP3 , an effector of apoptosis 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using dual-luciferase reporter assay, bta-miR-98 was observed to act with Caspase-3. Through overexpression of bta-miR-98, caspase-3 signaling was inhibited, leading to lower apoptosis and suppression of CPIV3 replication [37] . Additionally, X Fei et al examined regulatory alterations on proliferation, migration, invasion, and apoptosis of hepatitis B virus-related hepatocellular carcinoma (HBV-HCC) caused by miR-98.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Inducing apoptosis: CPIV3 infection induces apoptosis in both MDBK cells and goat tracheal epithelial cells by activating both the intrinsic and extrinsic pathways, which subsequently increases CPIV3 replication. Mechanistically, the ability of CPIV3 to induce apoptosis is mediated by the N protein [74,75]. One of the host cellular miRNAs, bta-miR-98, which markedly reduces CPIV3 replication by regulating apoptosis, is downregulated during CPIV3 infection and promotes viral replication.…”
Section: Virus-host Interactionmentioning
confidence: 99%